2014
DOI: 10.12659/msm.891235
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Adhesion Molecule-1 K469E Polymorphism and Risk of Coronary Artery Disease: A Meta-Analysis

Abstract: BackgroundIntercellular adhesion molecule-1 (ICAM-1) K469E polymorphism has been implicated in susceptibility to coronary artery disease (CAD). Several studies investigated the association of this polymorphism with CAD in different populations but the results were contradictory. A meta-analysis was conducted to assess the association between ICAM-1 K469E polymorphism and CAD susceptibility.Material/MethodsDatabases including PubMed, EMBASE, China National Knowledge Infrastructure (CNKI), and Weipu Database wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…We think previous meta-analyses [ 41 , 42 ] had several limitations. First, Li et al [ 42 ] and Zou et al [ 43 ] falsely extracted genotype data from included studies. [ 7 , 26 , 30 , 32 ] For instance, the correct genotype numbers from a Chinese study by Shang et al [ 7 ] were as following: case, AA = 48, AG = 50, GG = 24; control, AA = 29, AG = 33, GG = 35, but unlike the extracted data of these previous meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We think previous meta-analyses [ 41 , 42 ] had several limitations. First, Li et al [ 42 ] and Zou et al [ 43 ] falsely extracted genotype data from included studies. [ 7 , 26 , 30 , 32 ] For instance, the correct genotype numbers from a Chinese study by Shang et al [ 7 ] were as following: case, AA = 48, AG = 50, GG = 24; control, AA = 29, AG = 33, GG = 35, but unlike the extracted data of these previous meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 , 26 , 30 , 32 ] For instance, the correct genotype numbers from a Chinese study by Shang et al [ 7 ] were as following: case, AA = 48, AG = 50, GG = 24; control, AA = 29, AG = 33, GG = 35, but unlike the extracted data of these previous meta-analyses. [ 42 , 43 ] We also suspected the correctness of data from 2 studies. [ 30 , 32 ] Therefore, we re-conducted the meta-analysis combined with the correct data of these studies included by previous meta-analyses (not containing these new emerging studies).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several meta-analyses investigated the association between ICAM-1 rs5498 polymorphism and CAD before [ 26 29 ]. They all indicated that rs5498 polymorphism was a risk factor for CAD [ 26 29 ]. Among these meta-analyses, only one study by Li et al .…”
Section: Discussionmentioning
confidence: 99%